ANALYSIS OF HEALTH SURVEILLANCE PROCEDURES IN THE HEALTH REGION OF CEARÁ - da Silva, Wilson Borges; da Silva Barbosa, Rosimary (Cadernos ESP, 2023)
The activities developed by (VISA) cover several areas of knowledge, which work in an articulated way, so that its action results in “risk prevention and control, protection and health promotion, whether in the private or public sphere. The objective of this work was to analyze procedures related to the Sanitary Surveillance of the ADS municipalities of Aracati. The scenario was: Aracati, Fortim, Icapuí, Itaiçaba. Descriptive, quantitative research. The procedures related to: Inspection of establishments subject to VISA were analyzed; educational activities for the population; registration of establishments subject to VISA; educational activities for the regulated sector; receipt of complaints and treatment of complaints, establishment of sanitary administrative processes. Convergent and divergent procedures can be observed in some ADS municipalities. It is concluded that the municipalities presented the seven relevant procedures for health surveillance. It is suggested an intensification regarding the records of the procedures, since it was found that the SIA/SUS presents weaknesses, such as under-registrations, in addition to municipalities that did not register data in the system regarding the VISA procedures. This description appears as a limitation of the study.